Relationship Between Symptom Distress and Fatigue Characteristics in Patients with Gastric Cancer During 1 Month after Gastrectomy. (March 2022) - Yang, Hui-Ying; Lee, Yun-Hsiang; Wu, Jin-Ming; Lai, I-Rue; Shun, Shiow-Ching
This study's purpose was to describe changes in symptom distress and fatigue characteristics identifying which symptoms significantly impacted fatigue characteristics of patients with Gastric Cancer (GC) within 1 month after gastrectomy. A prospective longitudinal study was conducted. Patients with GC who were scheduled for gastrectomy were recruited from surgical outpatient clinics and surgery wards in northern Taiwan. Data were collected using a set of questionnaires before (T0) and 7 (T1) and 28 days (T2) after gastrectomy. Over all, 86 patients experienced mild levels of fatigue and symptom distress. The changes in worst fatigue and fatigue interference were greatest at T1. Anxiety had a significant negative effect on both worst fatigue and fatigue interference. Dry mouth, pain, and body image had significant deleterious effects on worst fatigue. The co-occurring symptoms affecting fatigue for patients with GC in the acute phase after gastrectomy should be actively assessed to ensure optimal fatigue management.